PERMINTAAN EKOWISATA WISATAWAN MANCANEGARA DI TAMAN NASIONAL BROMO TENGGER SEMERU (TNBTS), JAWA TIMUR [Ecotourism Demand of International Tourists at Bromo Tengger Semeru National Park (BTSNP), East Java] - Lambok P. Sagala; E.K.S. Harini Muntasib; Novianto Bambang W. (Media Konservasi, 2008)
Indonesian Government through Ministry of Culture and Tourism has set year of 2008 as the Indonesian visit year in which the target of international tourists visit was as many as 7 million tourists. However, eventhough the target has been set up, Indonesia still lack of data regarding tourism demand especially for ecotourism, while ecotourism has become a trend and interesting for many tourist which could attract more international tourists to come. Bromo Tengger Semeru National Park (BTSNP) is one of the most familiar Indonesian ecotourism destinations. The aim of the research was to get the illustration about international tourists demand at BTNSP. Research was conducted by interviewing international visitors. The respondents were selected using purposive sampling technique. Collected data was descriptively analyzed. Some findings of this research were international tourists who visited BTNSP was dominated by Ducth tourists (32%), man (61%), university graduated (69%), unmarried (63%), 25-31 years old (36%), employed (71%), using rent transportation (100%), the activity was to see the crater of Bromo (100 tourists), duration of stay was 1 day (60%), period of visit was during vacation day (99%), group tour (81%), stayed on the hotel (91%), first visit (95%), motivation was sightseeing/vacation (47%) and media as a source of information (54%). All tourists felt satisfied after enjoying natural scenic, got well services and felt safe. Some of the tourists (29%) thought BTNSP was dirty, 13% tourists thought accessibility was quite difficult and 13% thought that facilities in BTNSP were incomplete. Demand has no correlation with income, travel expenditure, leisure time, time duration to reach BTNSP and number of family.Keywords: Ecotourism, demand, international tourists, Visit Indonesia Year 2008, national park